2020
DOI: 10.1080/19390211.2020.1832640
|View full text |Cite
|
Sign up to set email alerts
|

Ingesting a Post-Workout Vegan-Protein Multi-Ingredient Expedites Recovery after Resistance Training in Trained Young Males

Abstract: Post workout multi-ingredient admixtures are commonly used to maximize recovery after exercise. The present double-blind, cross-over study compared the acute effects of ingesting a protein-vegan multi-ingredient (VGMT) vs. maltodextrin (MALT) on indices of muscle function. Ten trained males, (26.8±1.9 years) performed two identical, 3-day resistance training periods (one workout-session per day) while receiving either VGMT or MALT (10 minutes after the completion of each workout). Following a baseline evaluati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 32 publications
0
6
0
2
Order By: Relevance
“…The reason for not showing significant differences between the two supplemented groups in our study in cyclists could be because supplementation pre-training has shown improvements in mainly anaerobic exercise [27], and supplementation post-training has benefited endurance exercise [14,56]. Our cyclists practice a multimodal sport due to the demands of the varied routes and, therefore, use aerobic metabolism on the flat or anaerobic metabolism when sprinting and climbing mountains [18].…”
Section: Discussionmentioning
confidence: 90%
“…The reason for not showing significant differences between the two supplemented groups in our study in cyclists could be because supplementation pre-training has shown improvements in mainly anaerobic exercise [27], and supplementation post-training has benefited endurance exercise [14,56]. Our cyclists practice a multimodal sport due to the demands of the varied routes and, therefore, use aerobic metabolism on the flat or anaerobic metabolism when sprinting and climbing mountains [18].…”
Section: Discussionmentioning
confidence: 90%
“…According to Naclerio et al (2020), other concerns that make athletes seek supplements are to obtain healthy habits, post-training recovery and competition, or to increase their energy.…”
Section: Discussionmentioning
confidence: 99%
“…Post-entrenamiento: Los suplementos MTN post-entrenamiento contienen proteínas de alta calidad (por ejemplo, suero de leche, caseína, carne de vacuno), hidratos de carbono y una variedad de ingredientes sinérgicos como creatina (18), vitamina D (19), ácidos grasos omega-3 de cadena larga (2), aminoácidos esenciales, en particular leucina (19) y derivados como ?-HMB y L-carnitina (20). Las fórmulas postentrenamiento se utilizan para acelerar la recuperación tras el ejercicio y maximizar los resultados del entrenamiento (por ejemplo, aumento de masa muscular, fuerza o rendimiento de resistencia) (21).…”
Section: Efectos De La Suplementación Con Múltiples Ingredientes Para...unclassified